Unshackling South African artisanal miners: Considering Burkina Faso's legislative provisions as a guideline for legalisation and regulation - Wilson, Laura-Anne (Department of Private Law, 2019)
Artisanal mining in South Africa is not recognised as a legal activity in the primary legislation regulating mining, the Mineral and Petroleum Development Act (MPRDA) 24 of 2002. This contrasts with the reality in Burkina Faso, and numerous African jurisdictions, where mining provisions regulate this rudimentary form of small-scale mining. Without formal recognition, the socio-economic potential of artisanal mining to create jobs and sustain livelihoods is not realised. This is a missed opportunity to increase employment opportunities South Africa’s mining industry which, in response to falling commodity prices and rising labour costs, is experiencing significant retrenchments annually. This dissertation argues for an explicit artisanal mining provision in the MPRDA. The existing mining permit, which provides for small-scale mining activities, does not specifically include this basic manual activity. In fact, the mining permit requirements that small-scale miners must satisfy to operate legally are too onerous to comply with. The overarching recommendation is an ‘Artisanal and Small-Scale Mining (ASM) for SA Strategy’, involving the amendment of the existing policy and legal framework regulating both artisanal and small-scale mining, and the improvement of accompanying support initiatives. It is based on the premise that the revision of mining regulations, to recognise the rights of artisanal and small-scale miners, is an essential feature of the formalisation of ASM operations. Drawing on the experience in Burkina Faso specifically, and sub-Saharan Africa generally, this dissertation explores the persistence of ASM and why it often occurs informally. The overlap between informality and illegality is notoriously vague, particularly in South Africa where legislative distinctions are lacking. This research, initiating studies in a field of law that lacks comprehensive examination, attempts to highlight the nuances of ASM activities in South Africa, and how they can be integrated into the formal sector. These range from subsistence artisanal mining that is driven by poverty, to the artisanal mining forming part of international criminal syndicates. Both are illegal, but only one group intends to be. It is proposed that the regulation of artisanal mining in South Africa can harness its potential to create employment opportunities, generate state revenue, mitigate the negative environmental and health and safety consequences of ASM, fulfil the transformative objects of the MPRDA and help address the issue of illegal mining currently threatening the mining industry. To realise this potential, however, ASM operators need to overcome the challenges that prevent them from operating sustainably in the formal sector. Namely, bureaucratic and costly application processes, financial and technical constraints, a lack of business knowledge and access to markets, and a prevailing absence of institutional support. This dissertation explores these challenges and highlights the support initiatives needed for their redress. It further articulates the areas for future research which, along with legislative amendments and accompanying support, will help develop the ASM sector for the benefit of historically disadvantaged South Africans.